Scale validation: a case of behavioural intention to use mobile banking (Acta Universitatis Danubius. Œconomica, 2022)
Traditional retail banks face fierce competition from disruptive mobile innovations, consequently driving these conventional banks to invest more resources in mobile channels to maintain and sustain a competitive edge. Among the mobile innovations that revolutionised retail banking is mobile banking, which offers considerable convenience as financial services can be used without the physical access requirements of traditional banking. A validated scale is required to grasp better South African consumers' behavioural intention to use mobile banking. Therefore, this paper aimed to validate a scale measuring mobile banking behavioural usage intention, which, following a comprehensive search of the major academic databases, currently lacks in the South African context. To breach this literature gap, a survey questionnaire was completed by mobile banking consumers (N=334) who use mobile banking. The data was then analysed using analysis of moment structures (AMOS) software. The confirmatory factor analysis results produced in AMOS showed that the behavioural-intention-to-use mobile banking scale is a reliable, valid and well-fitting six-factor structure comprising attitude, perceived behavioural control, self-efficacy, trust, behavioural intention and structural assurances. As the first validated mobile banking behavioural usage intention scale in South Africa, this six-factor scale or structure can be used in path analysis to assess further which factors directly or indirectly predict mobile banking consumers' behavioural tendencies to use mobile banking.